Patient perspectives on practice guidance in nursing education : a scoping review - Glodek, Andrea [Verfasser]; Dauer, Bettina [Verfasser]; Reuschenbach, Bernd [Verfasser] (My University, 2026)
“Background: Practical training in health care involves caring for patients in hospitals, long-term care facilities, and outpatient settings. This scoping review examines patients’ perspectives on their involvement in clinical teaching and explores how evidence from medical education can guide nursing education when research is lacking. Methods: A systematic search of PubMed, CINAHL, and LIVIVO was conducted. Studies published in German and English that addressed clinical practice education in nursing and medicine were eligible. A total of 1,984 articles were screened based on the inclusion and exclusion criteria, of which 45 met the established criteria. Because no nursing-specific studies were identified during the initial search, the review was expanded to include medical education literature. This decision was based on the parallels between nursing and medical training, particularly regarding clinical competencies and patient-centred care. Results: The 45 extracted records provided findings on five topics: (1) Motivations for participation: Patients reported both altruistic motives (contributing to education) and personal benefits (increased attention and educational value). Acceptance rates ranged from 78–100% in most studies. (2) Barriers to participation: Privacy concerns dominated, particularly for intimate examinations, with strong gender-concordance preferences. Concerns about competence and cultural/religious factors also influenced willingness. (3) Patient experiences: Experiences were generally positive; however, physical discomfort, inadequate supervision, and boredom were reported. (4) Information and consent: Many patients lacked awareness of teaching contexts, role hierarchies, and their right to refuse participation, with some reporting feelings of coercion. (5) Organizational factors: Small group sizes, appropriate timing, and clear role communication enhanced patient experiences. Conclusions: No nursing-specific evidence is available on patient perspectives on clinical teaching. While medical education findings suggest that patients generally accept student involvement when privacy, communication, and consent are respected, the direct applicability to nursing contexts—particularly in outpatient, long-term care, and home settings—remains unvalidated. Nursing-specific research examining patient perspectives across diverse care settings is urgently needed to develop ethical, evidence-based guidelines for clinical education.” (authors’ abstract; BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; 370; 610; Pflegeberuf; Berufsausbildung; Praxisanleitung [Pflege]; Patient; Zufriedenheit; Literaturanalyse